(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2025)
This article highlights the importance of rare book collections in preserving scientific and cultural heritage. Rare books are not only invaluable sources reflecting national history and culture, but also serve as a means of transmitting intellectual and cultural wealth to future generations. The article analyzes the relevance of these collections, their preservation, and their role as sources for research. Modern technologies, particularly digitization processes, play a crucial role in safeguarding the physical condition of rare books and ensuring their effective use. Furthermore, the article examines the contribution of rare book collections to cultural and scientific development and offers recommendations for their preservation.